Seaweed Diversity in the Waters of Pantai Tanjung Api Paloh West Kalimantan - Safitri, Ikha; Warsidah, Warsidah; Sofiana, Mega Sari Juane (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
Paloh, one of West Kalimantan's conservation areas, has a high biodiversity of marine resources, including seaweed. Seaweed has an important ecological role, such as increasing primary productivity, providing dissolved oxygen, as a food source, and as a habitat for several aquatic organisms. In addition, seaweed contains various bioactive compounds that have the potential to be used in various industrial fields. This research aimed to identify the variety of seaweed in the waters of Pantai Tanjung Api, Paloh District, Sambas Regency, West Kalimantan. Based on the abundance of seaweed, the sampling site was chosen. A quadratic transect measuring 10x10 m2 was used for the collection. Four seaweed genera were discovered, including Acetabularia, Ulva, Padina, and Sargassum. Ulvophyceae and Phaeophyceae had the same percentage contribution. The species abundance varied between 1.04-26.75 ind/m2, where Padina had the highest value. Paloh has a low level of seaweed diversity, high uniformity, and a low dominance index.